HPTLC Method for Estimation of Ursolic Acid in Ocimum sanctum Extract - RAJ, BINCY; KHANAM, SALMA; LENO JENITA, JOSEPHINE (Asian Journal of Chemistry, 2010)
A quantitative HPTLC method was developed for the estimation of ursolic acid in Ocimum sanctum extracts. The ursolic acid was separated from plant extracts on a silica gel 60 F254 pre coated plate using a saturated mixture of toluene:ethyl acetate:glacial acetic acid in the ratio of 5.5:4.5:0.2 was used as mobile phase for estimation ursolic acid. Validation of the method was done in terms of LOD, LOQ, linearity, precision and accuracy. The repeatability of methods was excellent and average recovery was in the range of 100.43-102.12 %. The result of all parameter was within the limit. The methods were found to sensitive, simple and accurate. In the present study, the samples of Ocimum sanctum were collected from various geographical sources that is from Kerala, Karnataka and Kolkata. The method could satisfactorily quantify aqueous and aqueous methanolic extracts of samples from various geographical sources. The sample collected from Kerala was found to contain more amounts of ursolic acid.